Access, boundaries and confidence: The ABC of facilitating continuity of care experience in midwifery education - McKellar, Lois; Charlick, Samantha; Warland, Jane; Birbeck, David (Women and birth : journal of the Australian College of Midwives, 2014)
To register as a midwife in Australia, students must complete minimum requirements of clinical experiences throughout their programme. This includes following women through their childbirth journey in order to gain continuity of care experience. Research suggests that women and students find the continuity of care experience (COCE) valuable. Nevertheless, students cite difficulty in achieving these experiences. Aim This project sought to explore the challenges and identify supportive strategies for midwifery students undertaking the COCE. This project adopted an action research approach incorporating the four stages of planning, action, observation and reflection. This paper specifically reports the findings from the planning stage in which a focus group with education providers, facilitator and students was conducted and a survey with students (n=69) was undertaken. Key themes were identified through thematic analysis and a number of actions were proposed. Three main themes, ‘access’, ‘boundaries’ and ‘confidence’ were identified as challenges for students undertaking the COCE. Students raised concern regarding lack of access to women for COCE. They identified a need to establish clear professional and personal boundaries in managing the COCE. Students also highlighted the significance of confidence on the success of their experience. Throughout the study students identified strategies that could assist in the COCE. There is a need for clarity and support around the COCE for all stakeholders. Placing the COCE within a Service Learning model is one response that ensures that this experience is understood as being symbiotic for women and students and enables supportive actions to be developed and implemented.